TEACHING ACTIVITY LEARNING SYSTEM SCHEDULE SMA NEGERI 79 JAKARTA USING MICROSOFT VISUAL FOXPRO 9.0 - Maryana Ningsih; Rev. Linda Widianti, Skom., MMSI (Jurnal Sistem Informasi, 2008)
The school was established for the process of learning and teaching each studentwould be trained and guided by teachers to be able to behave politely and be moreforward thinking. SMA 79 Jakarta, is a school that has high discipline and good.Learning system SMA 79 Jakarta aims to facilitate the performance of teachers at aschool. System programming schedule of activities designed to help students at theschool, 79 high schools. To create a system program, the computer is a tool that isconsidered important. The program schedule system of teaching and learningactivities of this 79 state high schools created using Microsoft Visual Foxpro 9.0.Because by using Microsoft Visual FoxPro 9.0 system of teaching and learningactivities schedule 79 high schools became more easily designed to utilize the variousfacilities provided by Microsoft Visual Foxpro 9.0. So the system is easy to use.